Fucophlorethol C, a phlorotannin as a lipoxygenase inhibitor. Issue 12 (2nd December 2015) - Kurihara, Hideyuki; Konno, Remi; Takahashi, Koretaro
Abstract: Fucophlorethol C, a phlorotannin, was isolated from the brown alga Colpomenia bullosa (Scyto-siphonaceae) as a novel lipoxygenase (LOX) inhibitor. It was obtained as a free form from natural origin for the first time. The compound inhibited a soybean LOX to the same extent as the known inhibitor nordihydroguaiaretic acid.